The contiguous United States in eleven zip codes: identifying and mapping socio-economic census data clusters and exemplars using affinity propagation. Issue 1 (1st January 2020) - Heumann, Benjamin W.; Liesch, Matthew E.; Bogen, Nicholas R.; Meier, Ryan A.; Graziano, Marcello
ABSTRACT: The United States is a diverse and heterogeneous place. Accurately organizing and mapping the U.S. into different regions based on characteristics such as wealth, race, education, language, and occupation is a complicated and arduous task. This paper demonstrates the application of affinity propagation to map socio-economic patterns and identify representative exemplars. Affinity propagation clusters data based on representative exemplars and considers all data points as potential cluster exemplars. We use socio-economic data from the United States census to cluster zip codes tabulation areas and identify representative locations of socio-economic diversity of the United States. The 11 socio-economic clusters were mapped individually and together using area-based generalization. Mapping the results illustrated distinct regionalization and historical migration trends within the United States as well as national urban/suburban/rural patterns. Future applications of this technique may be useful for data-driven socio-economic analysis and purposive sampling.